(untitled) - Brown, Lester R. (New York, 1999)
This annual volume from the Worldwatch Institute shows in graphic form key trends that often escape the attention of the news media, world leaders, and economic experts, but should be integrated into their plans as they map out our global future.
Keywords: Nông nghiệp,Agriculture